Menumbuhkan Karakter Peserta Didik melalui Pendidikan Multikultural Pada Pembelajaran Seni Budaya - Rizal Wahyu Bagas Pradana (International Consortium of Education and Culture Research Studies, 2018)
In this era of globalization, education art and culture have an important role in the formation of the character of students. Therefore, it needs a learning-based multicultural art and culture as solutions in tackling the problem in the characters of adult learners. This is important as part of an effort to prevent menangulangi and radicalism, separatism, ethnic conflict to religion, and in an effort to cultivate an attitude of heterogeneity, plurality, appreciate cultural diversity and love of the motherland. In the study of art and culture-based multicultural education there are three aspects in it, the third aspect of this is that later will be able to successful multicultural education. In the absence of these three aspects is very unlikely to achieve the multicultural learning, the third aspect is the aesthetics, appreciation, and humanization. The existence of these three aspects will make it easier to maximize the development of the realm kognititf, psychomotor, affective and student as solution character education through multicultural education.